1977
DOI: 10.1111/j.1545-5300.1977.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Perception in Addict Families

Abstract: A technique called the "Interperception Matrix" was devised to investigate interpersonal perception in eight families in which addicted offspring maintained close parental ties. The addict families were compared with eight matched control families. Several differences were found between the two types of families. In addict families: (a) addicts, their fathers, and their mothers all held the addicts in low regard; (b) addicts were described as very different from their parents; (c) parents and addicts disagreed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This view, which regards the adolescent user as weak and inadequate, drives the parents to adopt a 'double-standard of values', one for themselves and another for their children. This double standard predominates in the field of drug use (Reilly, 1975;Alexander & Dibb, 1977). The adolescent rationalises his or her use through comparisons with the drinking parent.…”
Section: Resultsmentioning
confidence: 98%
“…This view, which regards the adolescent user as weak and inadequate, drives the parents to adopt a 'double-standard of values', one for themselves and another for their children. This double standard predominates in the field of drug use (Reilly, 1975;Alexander & Dibb, 1977). The adolescent rationalises his or her use through comparisons with the drinking parent.…”
Section: Resultsmentioning
confidence: 98%
“…An overall Family Effectiveness score is also obtained. Alexander and Dibb (1) used the Family Concept Q Sort to compare interfamily perceptions of the families of drug addicts and controls. The addicts and their parents described the addict as more passive and dependent than their ideals.…”
Section: Scope Of the Review And Bibliographymentioning
confidence: 99%
“…Several studies have demonstrated that addicts perceive their fathers as weak, uninvolved or absent, supplying harsh and inconsistent discipline (63, 104, 115). Alexander and Dibb (1) compared interpersonal perceptions within addict and control families and found that addicts were held in lower regard and thought to be too passive and dependent by the addict as well as his or her parents. The authors suggested that these perceptions undermined the addict’s self-esteem and tended to perpetuate the addiction.…”
Section: Family’s Impact On Mental Healthmentioning
confidence: 99%
“…The risk of drug abuse has also been approached by identifying those characteristics of “healthy” families with little or no drug abuse. In these families, offspring perceive more love from their parents (66); there is less discrepancy between parental perceptions and ambitions for their children (2); parents are more compatible with their children’s friends, exerting more influence on their children than peers do (29); both parents and peers are less tolerant of drug use (29); families function more democratically with better communication, more spontaneous agreement, deliberate decisionmaking, and cohesion (12, 39); families demonstrate more traditionalism and religiosity, respect for God and country, and transgenerational family pride; families practice authoritative, family-centered child-rearing emphasizing togetherness and cohesion, discipline, self-control, but less freedom for their children; they also demonstrate more teasing, and having fun together (9). Some of these “healthy” families have been characterized as “benevolent dictatorships” with elements of rigidity and “adamant beliefs that the status quo is right, that racial segregation is desirable, and that those who want social change are menaces” resulting often in “smug, dogmatic” children (9).…”
Section: Modes Of Primary Prevention Of Drug Abuse In Primary Carementioning
confidence: 99%